'Made in China': A reevaluation of embodied CO2 emissions in Chinese exports using firm heterogeneity information. (15th December 2016) - Liu, Yu; Meng, Bo; Hubacek, Klaus; Xue, Jinjun; Feng, Kuishuang; Gao, Yuning
Highlights: Firms in the same IO sector for China may have very different carbon intensity. Firm heterogeneity information significantly improves carbon footprint estimation. Embodied CO2 emissions in Chinese exports may be overestimated by 20% for 2007. The competitiveness of China's exports relates to upstream firms' externalities. Abstract: Emissions embodied in Chinese exports might be lower than commonly thought, which would increase China's responsibility for carbon emissions under a consumption-based approach. Using an augmented Chinese input–output table in which information about firm ownership and type of traded goods are explicitly reported, we show that ignoring firm heterogeneity causes embodied CO2 emissions in Chinese exports to be overestimated by 20% at the national level, with huge differences at the sector level, for 2007. This is because different types of firms that are allocated to the same sector of the conventional Chinese input–output table vary greatly in terms of market share, production technology and carbon intensity. This overestimation of export-related carbon emissions would be even higher if it were not for the fact that 80% of CO2 emissions embodied in exports of foreign-owned firms are, in fact, emitted by Chinese-owned firms upstream in the supply chain. The main reason is that the largest CO2 emitter, the electricity sector located upstream in Chinese domestic supply chains, is strongly dominated by Chinese-owned firms with very high carbon intensity.